Q&A with Piotr Chizinski, Head of Media Arts at the Solomon R. Guggenheim Museum, New York. - Chizinski, Piotr (Art in America, 2019)
An interview with Piotr Chizinski, head of media arts at Solomon R. Guggenheim Museum in New York City is presented. He discusses the various forms of technology and casting materials that he uses to create sculptures. He describes how he adapts older technologies to contemporary exhibition design. He talks about his experience working with artist Peter Fischli in 2016.